Ethics and politics in early childhood education - Dahlberg, Gunilla, 1945- (Contesting early childhood., 2005)
By drawing upon the 'Reggio approach', other post-structural theories and new thinking about democratic politics and power, this book sets out to explore the ethical and political dimensions of early childhood services. With governments worldwide looking for 'returns' through their 'investment' in services for children, the authors argue that the importance of these services are reduced to technical and managerial matters, without informed consideration for what is best for the child.